2007
DOI: 10.1021/ja0727363
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of TcO2by Neutron Powder Diffraction and First-Principles Calculations

Abstract: Crystalline technetium dioxide was prepared and for the first time its crystal structure determined by neutron powder diffraction. In addition, electronic structure calculations using density functional theory were performed to further elucidate the bonding mechanisms in TcO2. The crystal structure determined by Rietveld analysis with the NPD data is of a distorted rutile type, similar to that of MoO2; space group P21/c, a = 5.6891(1), b = 4.7546(1), c = 5.5195(1) A, and beta = 121.453(1) degrees . The NPD ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 21 publications
4
62
0
Order By: Relevance
“…From a crystal-chemical point of view, the short-long Tc pairing scheme is based on a sensitive balance between crystal field stabilization (favoring an even distribution of Tc-Tc distances by stabilizing a more symmetric TcO 6 octahedron, t 2g 3 configuration) and valence electrons available to form a Tc-Tc metal bond (shortening one of the two Tc-Tc distances). 63,64 In contrast to the EXAFS-ITFA-derived Tc speciation in the magnetite system, which showed an effect of the initial Tc concentration, the Tc speciation of the mackinawite series established in the same way shows rather an effect of Tc surface loading: samples Mack-3 and Mack-6 with the highest loading of 900 ppm have the highest contribution of TcO 2 •xH 2 O(s), although it never exceeds 20%, while the TcS x -like phase prevails in all systems ( Table 5).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…From a crystal-chemical point of view, the short-long Tc pairing scheme is based on a sensitive balance between crystal field stabilization (favoring an even distribution of Tc-Tc distances by stabilizing a more symmetric TcO 6 octahedron, t 2g 3 configuration) and valence electrons available to form a Tc-Tc metal bond (shortening one of the two Tc-Tc distances). 63,64 In contrast to the EXAFS-ITFA-derived Tc speciation in the magnetite system, which showed an effect of the initial Tc concentration, the Tc speciation of the mackinawite series established in the same way shows rather an effect of Tc surface loading: samples Mack-3 and Mack-6 with the highest loading of 900 ppm have the highest contribution of TcO 2 •xH 2 O(s), although it never exceeds 20%, while the TcS x -like phase prevails in all systems ( Table 5).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…In contrast to the ternary and quaternary osmates the binary oxide OsO 2 belongs to a group of transition-metal dioxides, including IrO 2 , RuO 2 , PtO 2 , TcO 2 , and ReO 2 , which crystallize in the rutile structure and show metallic behavior [7][8][9][10]. Compared to the majority of SOC-driven 5d transitionmetal oxides, the electronic structure of the rutile binaries can be explained with crystal-field arguments put forward by Goodenough [11].…”
mentioning
confidence: 99%
“…These monotonically increase as a function of the R ionic radius due to the progressive enhancement of the volume and the associated decrease of the cooperative rotation of the TcO6 octahedra.PACS numbers: 75.47.Lx,75.50.Ee,75.30.Et,71.15.Mb Intermediately located between manganese and rhenium, technetium (5s 2 4d 5 ) shares with its isovalent neighbors the intriguing possibility to form oxides with a complex structural, electronic and magnetic phase diagram. However, the rare occurrence of natural Tc (Tc is essentially an artificial product of fission reactions) and the related radioactive risks (Tc is the lightest radioactive element, whose most abundant isotope, 99 Tc, decays with a half-life of 10 5 years), have made investigations of Tc-based oxides very sparse [1][2][3][4][5][6]. Overcoming these difficulties, Avdeev et al [5] and Rodriguez et al [6] have recently reported the successful synthesis of the first ever fabricated Tc-based perovskites, namely CaTcO 3 and SrTcO 3 .…”
mentioning
confidence: 99%